A Survey on the Degree of Satisfaction of Teaching Skill Learning of Mathematics Normal Students in Post Practice - Li, Hao; Yang, Zezhong (American Journal of Creative Education, 2020)
The post-practice of normal students is a popular practice mode at present. Teaching skill is the main content that normal students learn in practice. In order to promote the better development of post-practice, this study selected some interns of the post-practice of mathematics major in a Normal University in China and investigated the satisfaction of learning. The results show that mathematics normal students are satisfied with the learning of the teaching skills of four dimensions, which shows that they are generally satisfied with the post-practice, and their satisfaction is relatively high. However, the learning of some of the teaching skills has low scores, indicating that mathematics normal students are not very satisfied with the learning of these teaching skills and need to improve. Therefore, it is suggested that in the process of post-practice, colleges and guidance teachers should pay attention to strengthening the guidance of weak teaching skills such as writing teaching plans, so as to promote the better development of normal students.